(untitled) (American Journal of Islam and Society, 1993)
The Nordic Association of Middle East Studies, which was established in 1989 in Uppsala, Sweden, recently held its second conference. Delegates from Denmark, Sweden, Norway, and Finland participated. John O. Voll (who has with Swedish ancestors), chairman of the Middle East Studies Association (MESA), came as guest lecturer. The conference’s leitmotif was "Diversity and Unity of the Middle Eastern World," which was also the theme of Voll’s lecture. By reconceptualizing the understanding of Middle East as a holistic region, one in which sociopolitical, economic, and cultural patterns have been regarded within a narrow "Muslim" or "Islamic," framework, he objected to standardized concepts and generalizations. He used the case of the Egyptian peasant-how new developments and changed structures have transformed the peasant of the 1970s into the different peasant of the 1990s. He also argued that concepts themselves can be actors in history when they have been conceptualized. Thus they do not always describe reality ...